Implementasi Nilai-Nilai Pancasila Perspektif Kiai Haji Achmad Siddiq Guna Menanamkan Pendidikan Karakter Siswa Sekolah Dasar - Lestari, Maghfirotul Firmaning; Ichsan, Maulana (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This research is motivated by the decline in character education due to cultural transformation and digitalization of the times. As a result, many children are less concerned about the history of Indonesia, the figure of the Hero, and the children's nationalist attitude will be weakened. Character education continues to be abandoned little by little because of the lack of influence from learning in instilling character education values ​​in students. Therefore, researchers are interested in bringing up the title